Outcomes of Total Dose Infusion Therapy in Pregnant Women with Iron Deficiency Anemia - Kanwal, Aisha; Nigar, Roohi; Phulpoto, Maryam; Waryah, Yar Muhammad (Journal of Liaquat University of Medical & Health Sciences, 2021)
OBJECTIVE: This study was aimed to access the capability of total dose infusion iron therapy for maintaining the hemoglobin level in local pregnant women METHODOLOGY: A descriptive study was carried out by using non probability consecutive sampling type and duration of study started from June-December 2019 at BMC Hospital Kotri and Civil Hospital Karachi. A total of 227 pregnant women with iron deficiency anemia were included in this study for total dose infusion (TDI) iron therapy through intravenous and pregnant women with normal hemoglobin and iron level were excluded. The patients were selected on the basis of constructed Performa details, CBC, Reticulocyte count, serum ferritin and TIBC parameters were recorded and measured before and after the therapy. The results were recorded from day 1 to 14; data were analyzed through SPSS version 16 software. RESULTS: The positive outcome of total dose infusion in pregnant anemic patients of iron deficiency anemia was observed in 80.62% (183/227). The upper middle class and well- educated families were also on high risk of iron deficiency anemia, the quick and satisfactory results were also obtained from upper middle class and well-educated families. The 80% of patents gave a positive response with in 14days of TDI whereas only 20% required more than 14 days for maintaining their hemoglobin level. CONCLUSION: TDI is a safe, effective, a fast and quick method to restore the level of hemoglobin, especially in case of pregnancy to improve iron deficiency in pregnant anemic patients. KEY WORDS: Iron deficiency anemia, Total dose infusion, Hemoglobin level